Set-based design application on dates harvesting machine - Khandelwal, Priyansh; Al-Ashaab, Ahmed; Oad, Nirav Manishkumar; Kumar Masetty, Venkata Surendra; Yan, Pei; Abdelrahman, Mahmoud; Ali Alkhateeb, Abdullatif (Elsevier, 2024)
This paper explores the application of Set-based Design (SBD) in the design of a dates harvesting machine. Dates are a popular fruit with significant economic importance, especially in Saudi Arabia. However, the process of harvesting them is highly labour-intensive, and there is a need for an automated solution to improve efficiency and reduce costs. The study begins with a comprehensive review of the literature on other fruit-harvesting machines. The research then proposes an architectural design of a dates harvesting machine based on the understanding of the typical fruit harvesting machines. The dates harvesting machine design proposed in this study consists of several sub-assemblies. Each sub-assembly is designed as a set of alternatives, with different configurations of components, mechanisms and materials. The understanding of the customer requirements of typical date farms helped to identify the list of values that are essential to design the dates harvesting machine. These values were filtered and analysed using an analytical hierarchy process to define three key value attributes of ‘design performance’, ‘safety’ and ‘cost’. The SBD approach helped to evaluate all the possible combinations of subsystems to identify the optimal solution that meets the customer's requirements and constraints. The SBD methodology resulted in the generation of 576 alternative design configurations which were aggressively narrowed down to 48 design solutions and then into 4 solutions where the final optimized design was selected using the PUGH matrix. The narrowing down is based on the combination of trade-off curves, solution performance and the identified key-value attributes. The proposed dates harvesting machine design shows great promise in improving the efficiency and sustainability of harvesting dates, and it can be adapted for use in agricultural applications.
Keywords: Set-based design; Dates harvesting machine; Lean product development; Design concept